CDKN2A Depletion Causes Aneuploidy and Enhances Cell Proliferation in Non-Immortalized Normal Human Cells. (3rd July 2018) - Hélias-Rodzewicz, Zofia; Lourenco, Nelson; Bakari, Mariama; Capron, Claude; Emile, Jean-François
Abstract: Aneuploidy is a common feature of cancer cells and may contribute to cellular transformation and cancer development. In this study, we found that significant down-regulation of CDKN2A, CHEK2, CDCA8, TP53BP1, and CCNDBP1 led to chromosome imbalances in two diploid non-immortalized human cell lines; however, only CDKN2A inhibition enhanced cell proliferation and additionally up-regulated three cell cycle control genes: CDCA8, AURKA, and CCND. These results confirm that CDKN2A is a tumor suppressor gene driving human cancer development by inducing cell aneuploidy and cell cycle up-regulation.